Modification of graphene oxide film properties using KrF laser irradiation. Issue 23 (3rd April 2018) - Mortazavi, Somayeh; Mollabashi, Mahmoud; Barri, Rasoul; Jones, Kevin; Xiao, John Q.; Opila, Robert L.; Shah, S. Ismat
Abstract : Modification of various properties of graphene oxide (GO) films on SiO2 /Si substrate under KrF laser radiation was extensively studied. Abstract : Modification of various properties of graphene oxide (GO) films on SiO2 /Si substrate under KrF laser radiation was extensively studied. X-ray diffraction, X-ray photoelectron spectroscopy, Raman spectroscopy and the electrical resistance measurements were employed to correlate the effects of laser irradiation on structural, chemical and electrical properties of GO films under different laser fluences. Raman spectroscopy shows reduced graphene oxide patterns with increased I 2D / I G ratios in irradiated samples. X-ray photoelectron spectroscopy shows a high ratio of carbon to oxygen atoms in the reduced graphene oxide (rGO) films compared to the pristine GO films. X-ray diffraction patterns display a significant drop in the diffraction peak intensity after laser irradiation. Finally, the electrical resistance of irradiated GO films reduced by about four orders of magnitudes compared to the unirradiated GO films. Simultaneously, reduction and patterning of GO films display promising fabrication technique that can be useful for many graphene-based devices.